2006
DOI: 10.1210/en.2005-0981
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation of Adult Monkey Sertoli Cells through Activation of Extracellularly Regulated Kinase 1/2 Induced by Heat Treatment

Abstract: Sertoli cells play a key role in triggering and regulating the process of spermatogenesis. Failure of a Sertoli cell to mature functionally will presumably render it incapable of supporting germ cell survival and development that appeared after puberty. Expression of cytokeratin 18 (ck-18) intermediate filaments indicates a state of undifferentiation usually observed in Sertoli cells of prepubertal testis. In this study we demonstrated that local testicular heat treatment of adult monkey with water at 43 C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 59 publications
5
42
2
2
Order By: Relevance
“…In a study with adult monkeys, Zhang and colleagues (28) showed that local testicular heat treatment was able to activate the reexpression of CK18 in Sertoli cells, which was coincident with activation of extracellular signal-regulated kinase (ERK)1/2 and Akt kinases. After blocking the ERK mitogen-activated protein kinase (MAPK) signaling pathway, they observed an inhibition of CK18 expression, and they also detected this inhibitory effect by blocking protein kinase A (PKA) activation.…”
Section: Cell Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study with adult monkeys, Zhang and colleagues (28) showed that local testicular heat treatment was able to activate the reexpression of CK18 in Sertoli cells, which was coincident with activation of extracellular signal-regulated kinase (ERK)1/2 and Akt kinases. After blocking the ERK mitogen-activated protein kinase (MAPK) signaling pathway, they observed an inhibition of CK18 expression, and they also detected this inhibitory effect by blocking protein kinase A (PKA) activation.…”
Section: Cell Signalingmentioning
confidence: 99%
“…However, CK18 activation remained unaltered when the PI3K/Akt pathway was blocked. Zhang and colleagues (28) concluded that the heat treatment was able to induce a reversible change in the Sertoli cells from an adult differentiated state to an immature-like dedifferentiated state through PKA-ERK MAPK-dependent pathways, but not via the PI3K/Akt pathway. In another study, Gilbert and colleagues (29) showed that inhibition of ERK1/2 activation sensitized wild-type but not K8-null mouse hepatocytes to apoptosis, and a much weaker ERK1/2 activation occurred in CK8-null hepatocytes.…”
Section: Cell Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat treatment of the primary Sertoli cell culture isolated from the adult monkey testis at 43°C could also induce CK-18 reexpression. These results from in vivo and in vitro experiments demonstrated that heat treatment of adult monkey Sertoli cells was capable of inducing a reversible change in the Sertoli cells from an adult differentiated state to an immature dedifferentiated state (Zhang et al 2006). …”
Section: Dedifferentiation In Mammalsmentioning
confidence: 84%
“…: +86 1068210077; Fax: +86 10 68989955; E-mail: fuxiaobing@vip.sina.com ies suggest that dedifferentiation may be possible in mammalian system. It was reported that pancreatic cells, 1) renal epithelial cells, 2) retinal cells, 3) myoblasts, 4) neurons, 5) and germ cells 6) have the potential of dedifferentiation in response to appropriate signals or factors. Obviously, commitment to terminal differentiation is not an irreversible process.…”
Section: Introductionmentioning
confidence: 99%